A literature review on overtourism to guide the transition to responsible tourism - Buitrago-Esquinas, Eva María; Foronda-Robles, Concepción; Yñiguez-Ovando, Rocío (Revista de Estudios Andaluces, 2023)
Although the pre-pandemic tourism debate was led by Overtourism, when the pandemic erupted, the increasing literature on this topic was still in an initial stage. The mobility restrictions derived from Covid-19 stopped Overtourism, but the problem is still far from being eradicated. There is an increasingly need for a solid body of knowledge on which to build recovery to avoid making past mistakes. A comprehensive pre-pandemic literature review is carried out, by proposing an overtourism conceptual framework that integrates its causes and consequences. How the pandemic could become an opportunity to transition to a responsible tourism model is discussed.